The Effect of 6c Training for IGD Nurses on Increasing IGD Patient Satisfaction at ABL Hospital - noti, daud; Leo Bunga, Asnet; Tjitra, Emiliana (International Journal Labs, 2025)
The emergency department is the front line in treating patients. This study aims to determine the effect of 6C’s based services on patient satisfaction in the Hospital Emergency Department. ABL. Used pra experimental design with approach pre-posttest-in one group only, without control group design. The research subjects were all patients who sought treatment at the ER at RS ABL. The treatment used was 6C’s training for ER nurses at RS.ABL. Data were analysed using SPSS 24, the results of the paired sample t test found that there was an increase in the average patient satisfaction of 2.48 before and after the intervention with a p-value of 0.015<0.05 and there was an increase in the quality of 6C’s services regarding patient satisfaction, each item namely compassion, competence, confidence, conscience, commitment and comfort each increased significantly with a p value of 0.000<0.05 on patient satisfaction. the results of the linear regression test found that there was an influence of the characteristics of emergency room nurses and the quality of the 6C’s services on the satisfaction of emergency room patients at ABL Hospital. The results of the multivariate linear regression analysis showed that the significant variable (p-value: 0.05) was gender with a p-value of 0.002<0,05, compassion with a p-value of 0.032<0.05, Confidence with a p-value of 0.044<0.05, and Conscience with a p-value of 0.025<0.05. It was concluded that there was an influence of the 6 C's of emergency room nurses' training on the satisfaction of emergency room patients at ABL Hospital.